Role of halotolerant phosphate‐solubilising bacteria on growth promotion of peanut (Arachis hypogaea) under saline soil. (3rd December 2018) - Jiang, Huanhuan; Qi, Peishi; Wang, Tong; Chi, Xiaoyuan; Wang, Mian; Chen, Mingna; Chen, Na; Pan, Lijuan
Abstract : Soil salinity is a major abiotic stress that limits plant growth, and inoculating plant growth‐promoting rhizobacteria is a well‐known strategy to reduce stressors under adverse soil conditions. This study was conducted to assess the effect of halotolerant phosphate‐solubilising bacteria (PSB) on protecting peanut against salt stress. Four candidate strains: Bacillus megaterium (YM13), Enterobacter sp. (YM14), Providencia rettgeri (TPM23) and Ensifer adhaeren (TPMX5) showed strong tolerance to NaCl and high phosphate‐solubilising ability even at a NaCl concentration of 1.4 M. In addition, all four strains demonstrated variable levels of phosphate solubilisation activity in the presence of various carbon and nitrogen sources, indicating high phosphate‐solubilising efficacy. Germination and radicle length of peanut seedlings increased with inoculation of PSB under both control and saline conditions. Statistically significant increase in the root length (range: 25.71–49%), stem length (19–48%), number of leaves (12.5–37%) and root/shoot biomass were observed. This could be attributed to plant hormones (i.e., indole acetic acid [IAA], abscisic acid [ABA] and gibberellic acid [GA3]) and successful root colonisation by bacterial inoculants. Root colonisation was positively correlated to plant growth and shown to be influenced by soil conditions. In addition, the PSB also improved the levels of available P in soil. The most pronounced beneficial effect on the growth of peanut plants and soil available P content was observed in the inoculation of the PSB isolates with Ca3 (PO4 )2 addition. This is the first report that describes Providencia rettgeri as a plant growth‐promoting bacterium that may be utilised to alleviate the negative effects of salt stress on peanut plants. This bacterial species may thus be potentially used as a biofertilizer for sustaining the growth of peanut in salt‐stressed soil and in mitigating soil stress conditions. Abstract : We first demonstrated that the halotolerant phosphate‐solubilising bacteria (PSB) are useful in promoting peanut growth as well as levels of available P in soil. This could be attributed to plant hormones and successful root colonisation by PSB inoculants. In addition, the most pronounced beneficial effect on growth of peanut plants and soil available P content was observed in the co‐inoculation of the PSB isolates with Ca3 (PO4 )2 addition.